IJARAH, UJRAH, DAN ISTI’JAR DALAM PERSPEKTIF ILMU HADIS DAN HUKUM ISLAM - Mulkan Nasution; Fauzan Mas’ar; Muhari Syahlaili Saragih; Muhammad Taufiq Nasution (Albayan Journal of Islam and Muslim Societies, 2025)
The rapid development of Islamic economics in Indonesia has intensified the implementation of contracts based on ijārah, ujrah, and isti’jār in various business and financial activities. This article aims to analyze the concepts of ijārah, ujrah, and isti’jār from the perspective of hadith studies and to examine them within the framework of Islamic law. This research employs a qualitative library-based method. The methodology includes thematic hadith exploration, takhrīj al-hadith, sanad criticism, and matn criticism of narrations related to wage payment and leasing practices. The findings reveal that the hadith on ujrah is transmitted through several chains with varying degrees of authenticity; however, its substance does not contradict the Qur’an or other authentic hadiths. The narrations concerning ijārah and isti’jār demonstrate normative legitimacy for leasing and employment contracts, provided that they uphold justice, contractual clarity, and are free from elements of gharar and injustice. From the perspective of Islamic law, ijārah is analogically related to sale contracts since its object concerns usufruct (manfa‘ah), and its original ruling is permissibility unless there is evidence prohibiting it. This study affirms that the fulfillment of ujrah constitutes an imperative obligation linked to the protection of rights and the realization of maqāṣid al-sharī‘ah, particularly in safeguarding property and promoting social justice.